Protein nanoparticles induce the activation of voltage-dependent non-selective ion channels to modulate biological osmotic pressure in cytotoxic cerebral edema - Fan, Wei; Liu, Liming; Yin, Yuxuan; Zhang, Jiayi; Qiu, Zhaoshun; Guo, Jun; Li, Guangming (Frontiers in Pharmacology, 2024)
Introduction Cytotoxic cerebral edema is a serious complication associated with cerebral ischemic stroke and is widely treated using the hypertonic dehydrant. Here, we propose, for the first time, the decrease of intracellular osmosis as a treatment strategy for alleviating cytotoxic cerebral edema. Methods We established a fluorescence resonance energy transfer-based intermediate filament tension probe for the study and in situ evaluation of osmotic gradients, which were examined in real-time in living cells from primary cultures as well as cell lines. The MCAO rat model was used to confirm our therapy of cerebral edema. Results Depolymerization of microfilaments/microtubules and the production of NLRP3 inflammasome resulted in an abundance of protein nanoparticles (PNs) in the glutamate-induced swelling of astrocytes. PNs induced changes in membrane potential and intracellular second messengers, thereby contributing to hyper-osmosis and the resultant astrocyte swelling via the activation of voltage-dependent nonselective ion channels. Therefore, multiple inhibitors of PNs, sodium and chloride ion channels were screened as compound combinations, based on a decrease in cell osmosis and astrocyte swelling, which was followed by further confirmation of the effectiveness of the compound combination against alleviated cerebral edema after ischemia. Discussion The present study proposes new pathological mechanisms underlying “electrophysiology-biochemical signal-osmotic tension,” which are responsible for cascade regulation in cerebral edema. It also explores various compound combinations as a potential treatment strategy for cerebral edema, which act by multi-targeting intracellular PNs and voltage-dependent nonselective ion flux to reduce astrocyte osmosis.